Corporate strategies to exploit the social status created by advertising: quantity vs. price competition - Chieko Fujisawa (International Telecommunications Society (ITS), 2024)
When firms use advertising to differentiate their products and increase consumer appreciation of their products, the strategy, i.e., price or quantity, depends on the degree of product differentiation and the magnitude of advertising costs. If advertising costs in Bertrand competition are very much lower than advertising costs in Cournot competition, the firms will choose Bertrand competition. If advertising costs in Bertrand competition are comparable to advertising costs in Cournot competition, both firms will choose Cournot competition. If advertising costs in Bertrand competition are lower than those in Cournot competition, and differentiation is, to some extent greater, firms adopt different strategies each other. This is because firms take advantage of the different advertising effectiveness of competitors under the conditions of cost and differentiation increase profitability. There is also a mixed strategy option under these conditions. Furthermore, the differentiation strategy with advertising increases firms' profits and increases consumer surplus and total surplus compared to the case without advertising.
Keywords: D43; L13; M37; 330; Online media advertising; Mass media advertising; differentiation strategy; Cournot competition; Bertrand competition; Duopoly model